Outstanding student, education and attention to their special needs in the Costa Rican educational system. - D’Agostino Santoro, Giuseppa (2004)
The pages presented here areanalytical-descriptive reflection about education of outstanding and talented apprentice inacademic area. To do this, first made ​​a brief characterization of this type of student and provides a vision of educational alternatives moreapplied in teaching practice, for training. Then provides some state actions, made ​​at the policy level Costa Rican educational system to meet the needs ofthis group of students and their situation is evidentneglect in the current system. We conclude showing the presence of a reductionist viewspecial educational needs in the relevant legislation, which violates the philosophy ofinclusive education, and the right to diversity anda broad education of each and every one ofstudents.